Forward Osmosis: Temperature Effects By Using Pome as Feed Solution - Hanizah Arifin; Thomas SY Choong; Chan Kam Rong; Fakhru'l Al-Razi Ahmadun; Luqman Chuah Abdullah; Luqman Chuah Abdullah (ASEAN Journal of Chemical Engineering, 2015)
Forward osmosis (FO) has recently been considered as one of the promising technologies for low energy applications. Factors that influence FO performance are draw solution, types of membrane, membrane orientation, cross flow velocity, module configuration and temperature effect. In this study, the influence of temperature on the performance of FO process has been studied in terms of water flux by using raw POME as feed solution. A higher temperature creates a higher water fluxes at various draw solution concentrations. Percentages of water flux increments for raw POME are between 7% to 9% from 25ºC to 35ºC and 32% to 75% from 25ºC to 45ºC.